The role of craving in the treatment of alcohol use disorders: The importance of competing desires and pretreatment changes in drinking. (1st June 2019) - Schlauch, Robert C.; Crane, Cory A.; Connors, Gerard J.; Dearing, Ronda L.; Maisto, Stephen A.
Highlights: Effects of craving and competing motivations on drinking during treatment. Ambivalence was associated with decreased drinking for those initiating change. Ambivalence was associated with increased drinking for those maintaining change. Competing desires and pretreatment change are important for understanding craving. Abstract: Background: The current study aimed to contribute to the understanding of the session to session relationship between craving and drinking during the course of treatment via the incorporation into the analysis of both a) motivation to avoid alcohol and 2) pretreatment change, given that half of all individuals entering treatment change their drinking prior to the first session. Methods: Sixty-three treatment-seeking participants received 12 weeks of CBT for alcohol dependence and completed assessments of approach inclinations, avoidance inclinations and drinking behaviors at the end of each session. Results: Consistent with our hypothesis, motivations to avoid alcohol and pretreatment change significantly interacted with craving to predict both number of drinking days and heavy drinking days during the interval between sessions. Specifically, among lower pretreatment changers, motivation to avoid alcohol moderated the effect of craving on number of drinking days and number of heavy drinking days, such that craving positively predicted drinking among those lower on motivations to avoid only. In contrast, among higher pretreatment changers, cravings positively predicted drinking among those higher on motivations to avoid alcohol. Conclusions: These findings highlight the importance of measuring both desire to consume and desire to avoid consuming alcohol simultaneously, and suggest that ambivalence may function differently depending on whether one is initiating (low pretreatment change) versus maintaining change (high pretreatment change).